Peranan Manager Dalam Upaya Meningkatkan Kinerja Karyawan PT Sariguna Primatirta TBK di Desa Megati, Kecamatan Selemadeg Timur, Kabupaten Tabanan - Ni Luh Putu Vera Wikantari; Anak Agung Ketut Sri Candrawati (Jurnal Widya Mahavira, 2025)
This study analyzes the role of managers in improving the performance of employees of PT Sariguna Primatirta Tbk in Megati Village, East Selemadeg District. Managers play a key role in encouraging employee performance to achieve effective and efficient organizational goals, as well as driving motivation and directing employees. This qualitative descriptive research was conducted at PT Sariguna Primatirta Tbk Megati Branch, Tabanan-Bali. Primary data was obtained from informants selected using purposive sampling, including managers, QC analysts, operational admins, engineers, and employees. The results of the study identified three main roles of managers: (1) Interpersonal roles as figureheads, leaders, and intermediary officials; (2) Informational role as monitors, disseminators, and spokespersons; (3) The role of decisional makers as entrepreneurs, disruptors, resource distributors, and negotiators. The conclusion of the study shows that the role of managers has been well implemented and has made a significant contribution to improving employee performance. The role of leader, monitor, disseminator, disturbance handler, and negotiator has proven to be very influential in improving the performance of company employees.